Human trafficking - Cullen-DuPont, Kathryn (New York, NY : Facts On File, 2009)
"Despite the United Nations having officially abolished slavery and the slave trade more than 60 years ago, millions of human beings continue to be enslaved. Human trafficking - the official term for the modern-day slave trade - consists of buying and selling people with the intent of exploiting them through forced labor or sexual acts." "Human Trafficking provides a thorough examination of this issue. It describes the suffering caused by human trafficking as well as the financial and cultural conditionsthat make modern slavery possible, both within and beyond national borders. The efforts of the United Nations, national governments, and nongovernmental organizations to combat human trafficking are thoroughly discussed, as are those to provide direct aid to the individual victims. Human Trafficking is an eye-opening account that examines how the trade is conducted in the United States, the Netherlands, Nigeria, India, and Belize. Each case study analyzes the patterns of trade, the types of exploitation,why countries have failed to halt the practice, and the unrelenting efforts to eradicate human trafficking."--BOOK JACKET.
At issue. Human trafficking ; Historical overview ; Defining the victims of human trafficking ; The international exploitation of trafficked persons ; Causes of human trafficking ; International efforts to end human trafficking -- Focus on United States.The United States's role in trafficking ; Origins of persons trafficked to the United States ; Exploitation of trafficked persons in the United States ; Considerations particular to trafficking in the United States ; U.S. efforts to end human trafficking-- Global perspectives. Netherlands ; Nigeria ; India ; Belize -- Primary sources. United States documents. Legislation and executive orders ; Media, briefs, and press releases ; Forced labor and domestic servitude ; Sex trafficking ; Child sexual exploitation ; U.S. efforts to end human trafficking -- International documents. International treaties and declarations ; International accounts of human trafficking ; Netherlands ; Nigeria ; India ; Belize -- Research tools. How to research human trafficking. Researching chattel slavery ; Modern-day slavery -- Facts and figures. Human trafficking in the world ; Fighting human trafficking ; Global maps and routes ; Inequality and human trafficking -- Key players, A to Z -- Organizations and agencies -- Annotated bibliography. Belize ; Chattel slavery ; Child marriage, forced marriage, and Council-ordered punishment rapes/marriages ; Child soldiers ; Forced labor ; India ; Involuntary domestic servitude ; Netherlands ; Nigeria ; Poverty ; Scope and magnitude of international human trafficking ; Sex tourism ; Sex trafficking ; Trafficking for involuntary organ harvests ; Trafficking for infants ; United States.
Includes bibliographical references and index.
Keywords: Human trafficking; Forced labor; Child labor; Slavery